2015
DOI: 10.1093/brain/awv117
|View full text |Cite|
|
Sign up to set email alerts
|

De novopoint mutations in patients diagnosed with ataxic cerebral palsy

Abstract: Cerebral palsy is commonly attributed to perinatal asphyxia. However, Schnekenberg et al. describe here four individuals with ataxic cerebral palsy likely due to de novo dominant mutations associated with increased paternal age. Therefore, patients with cerebral palsy should be investigated for genetic causes before the disorder is ascribed to asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 91 publications
3
126
0
3
Order By: Relevance
“…Among the causative variants identified in the nine patients, the variants in SPAST , GNAO1 , CACNA1A, and STXBP1 have been previously reported,27, 28, 29, 30, 31, 32 whereas the variants in the other genes ( CTNNB1 , CYP2U1 , AMPD2 , and SCN2A ) were novel. Of all the identified candidate genes, only SPAST , STXBP1 , and SPTBN2 have been previously reported in CP patients 33, 34, 35. In five cases, we identified eight unknown significant candidate variants of five genes ( UBA1 , AMER1 , FAT4 , GPR98 , and SPTBN2 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Among the causative variants identified in the nine patients, the variants in SPAST , GNAO1 , CACNA1A, and STXBP1 have been previously reported,27, 28, 29, 30, 31, 32 whereas the variants in the other genes ( CTNNB1 , CYP2U1 , AMPD2 , and SCN2A ) were novel. Of all the identified candidate genes, only SPAST , STXBP1 , and SPTBN2 have been previously reported in CP patients 33, 34, 35. In five cases, we identified eight unknown significant candidate variants of five genes ( UBA1 , AMER1 , FAT4 , GPR98 , and SPTBN2 ).…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, case 17 was also a compound heterozygote of SPTBN2 variants. SPTBN2 has been identified in both autosomal dominant and autosomal recessive spinocerebellar ataxia,42 together with CP 34. Although both SPTBN2 variants in case 17 were classified as having uncertain significance and the patient's clinical presentation was consistent with SCN2A ‐related disorder, we cannot eliminate the possibility that those variants in SPTNBN2 could contribute to the patient's phenotype.…”
Section: Discussionmentioning
confidence: 90%
“…In order not to exclude variants of potential pathological significance, in the regulatory regions, promoters, UTRs, intron-exon splice sites should also be analyzed. Further filtering to identify causal mutations depends upon the mode of inheritance; for example, with a recessive disorder, one would necessarily focus on homozygous and compound heterozygous SNVs [13,14,15]. Single-nucleotide polymorphism (SNP) information embedded within the exome sequencing data has also been used for homozygosity mapping or analysis; this is important in order to narrow down regions harbouring the mutations underlying recessive disorders [16].…”
Section: Discovering Germline Variants For Rare Mendelian Disordersmentioning
confidence: 99%
“…It matters little that medicine today has almost no real knowledge concerning the length of time and degree of hypoxemia required to produce CP or any other neurologic injury in a previously healthy fetus [56,[59][60][61]. It does not matter either that fifty years of CP-EFM research has repeatedly proven asphyxia to be a cause of only a tiny fraction of CP cases, while the same research identified a multiplicity of antenatal-post-natal causative factors, a number of which are silent and impossible to recognize until years later [1-11, 21, 39, 56, 59-63] in addition to the most recent genetic studies revealing the large number of plausible mutations, de novo and inherited, contributing to cerebral palsy causation [10,64,65]. The public, trial lawyers, and a surprising number of physicians, including obstetricians, still believe the oxygen-deprivation-is-the-sole-cause-of-perinatalbrain-damage and CP myth [47][48][49][66][67][68][69][70][71].…”
Section: Journal Of Childhood and Developmental Disorders Issn 2472-1786mentioning
confidence: 99%